The Dynamics of Interaction and Values in Faith and Morals Education: A Study of the Inside Outside Circle Model at MIN 5 Cilacap - Firdaus, Asep Deny (Shibyan: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
Background: Character education in elementary schools faces a serious challenge: the dominance of conventional teaching methods with minimal interaction, which hinders the internalization of moral values. This study aims to analyze the effectiveness of the Inside Outside Circle (IOC) learning model in improving learning outcomes, social interaction, and the internalization of moral values in students. Methods: This qualitative case study involved a teacher and fifth-grade students at MIN 5 Cilacap. Data collection was conducted through participatory observation, in-depth interviews, and documentation. Data analysis used the interactive model by Miles and Huberman. Results: The implementation of IOC showed a significant increase in both cognitive and affective learning outcomes. Students' post-test scores increased by an average of 15 points, and they were able to connect moral concepts to real-life experiences. Socially, IOC created an inclusive and egalitarian classroom climate, where quiet students became more active. Active participation in discussions triggered self-reflection and fostered the authentic internalization of values, evidenced by daily behavioral changes such as increased discipline and empathy. Conclusion: The IOC model is proven to be an effective and holistic teaching strategy. It not only improves cognitive understanding but also facilitates meaningful social interaction and sustainable value internalization, transforming students into active agents in their own character development.